The relationship between dental status, food selection, nutrient intake, nutritional status, and body mass index in older people A relação entre estado dentário, seleção alimentar, ingestão de nutrientes, estado nutricional e índice de massa corporal em idosos - Wagner Marcenes; Jimmy George Steele; Aubrey Sheiham; Angus Willian Gilmour Walls (Cadernos de Saúde Pública, 2003)
This paper reviewed the findings from a national survey in Great Britain which assessed whether dental status affected older people's food selection, nutrient intake, and nutritional status. The survey analyzed national random samples of free-living and institution subjects for dental examination, interview, and four-day food diary as well as blood and urine tests In the free-living sample, intakes of non-starch polysaccharides, protein, calcium, non-heme iron, niacin, and vitamin C were significantly lower in edentulous as compared to dentate subjects. People with 21 or more teeth consumed more of most nutrients, particularly non-starch polysaccharides. This relationship in intake was not apparent in the hematological analysis. Plasma ascorbate and retinol were the only analytes significantly associated with dental status. Having 21 or more teeth increased the likelihood of having an acceptable body mass index (BMI). Thus, maintaining a natural and functional dentition defined as having more than twenty teeth into old age plays an important role in having a healthy diet rich in fruits and vegetables, a satisfactory nutritional status, and an acceptable BMI. Este artigo objetivou revisar os achados do levantamento epidemiológico conduzido no Reino Unido, cuja finalidade foi avaliar a relação entre saúde bucal, ingestão de nutrientes e estado nutricional. Uma amostra representativa dos idosos institucionalizados e não-institucionalizados foi examinada em relação à saúde bucal. Além disso, amostras de sangue e urina foram coletadas e entrevistou-se os idosos, ocasião em que se completou um diário alimentar de quatro dias. Na amostra de idosos não-institucionalizados, o consumo de polissacarídeos não-amido (fibras), proteína, cálcio, ferro nao-hemoglobina, niacina e vitamina C foi significantemente menor em edêntulos do que em não-edêntulos. Idosos com a presença de 21 dentes ou mais consumiram mais nutrientes, principalmente fibras. Ácido ascórbico e retinol plasmático estavam significantemente associados com saúde bucal. Concluiu-se que manter uma dentição natural funcional, definida como ter 21 dentes ou mais, desempenha um importante papel em ter uma dieta saudável rica em frutas, verduras e legumes, um estado nutricional satisfatório e um Índice de Massa Corporal aceitável.